2021
DOI: 10.1002/lsm.23464
|View full text |Cite
|
Sign up to set email alerts
|

Three‐step irradiance schedule versus two‐step irradiance schedule for pain control during topical 5‐aminolevulinic acid‐photodynamic therapy of facial acne in Chinese patients: A prospective randomized comparative study

Abstract: Background: A two-step irradiance schedule has been found to be useful for pain control during photodynamic therapy (PDT) on nonmelanotic skin cancer and condyloma acuminatum. Objectives: To evaluate the efficacy of a new three-step irradiance schedule derived from the psychological "peak-end rule" and two-step irradiance schedule in relieving pain during 5-aminolevulinic acid PDT (ALA-PDT) on acne. Methods: A total of 90 moderate to severe acne patients were enrolled in our study and randomly divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Among 2461 potential studies, 206 satisfied the inclusion criteria (eFigure in the Supplement). Among included trials, 163 (79%) were for acne and 43 (21%) were for rosacea. Rosacea RCTs were more likely to include at least 1 PROM (67% [n = 29 of 43]) compared with acne RCTs…”
Section: Resultsmentioning
confidence: 99%
“…Among 2461 potential studies, 206 satisfied the inclusion criteria (eFigure in the Supplement). Among included trials, 163 (79%) were for acne and 43 (21%) were for rosacea. Rosacea RCTs were more likely to include at least 1 PROM (67% [n = 29 of 43]) compared with acne RCTs…”
Section: Resultsmentioning
confidence: 99%
“…99 A 3-step irradiance schedule for ALA-PDT had similar acne clearance rates but significantly reduced pain (Visual Analogue Scale 1.61 vs 3.14; P < .0001) compared to a 2-step irradiance schedule with the same total irradiance dose of 84 J/cm 2 . 100 A comparative RCT found that ALA-PDT resulted in superior clearance rates of inflammatory acne lesions compared to IPL or blue-red LED light-based therapies (92% vs 58% or 44%; P < .01). 101 In a RCT of patients with moderate inflammatory facial acne, 2 sessions of ALA-PDT performed 2 weeks apart significantly reduced inflammatory lesions (84% vs 74%; P = .02) and total lesions (79% vs 67%; P = 0.026) at 12 weeks compared to patients that received daily oral doxycycline 100 mg and 0.1% adapalene gel.…”
Section: Acne Vulgarismentioning
confidence: 99%
“…Acne vulgaris PDT ↑ CR of inflammatory acne lesions compared to IPL or blue-red light-emitting diode phototherapy. 100 RCT ALA-PDT ↑ CR of inflammatory and total acne lesions compared to oral doxycycline and adapalene gel. 101…”
Section: Rctmentioning
confidence: 99%
See 1 more Smart Citation
“…If a small amount of liquid is inadvertently applied to the mucosal area, the photosensitizer must be removed thoroughly after bandaging in order to reduce residue as well as avoid postoperative redness and pain. 7 (3) Postoperative skin nursing: Immediate postoperative skin reactions include erythema and swelling. In the present study, medical cold compresses containing hyaluronic acid or antibiotic peptides were applied to the patients' faces and intermittently ice-packed for 30-60 min using a cold spray machine.…”
Section: The Observation Groupmentioning
confidence: 99%